1999
DOI: 10.1074/jbc.274.44.31150
|View full text |Cite
|
Sign up to set email alerts
|

Quinone Reductase Inhibitors Block SAPK/JNK and NFκB Pathways and Potentiate Apoptosis

Abstract: The MEKK1 protein kinase (2) is a proximate activator of the stress-activated protein kinase (SAPK, 1 alternatively known as JNK) stress-signaling pathway (3). A variety of environmental stresses, including inflammatory cytokines, hyperosmotic shock, and UV light, stimulate the cascade (4). MEKK1 is implicated in apoptotic cell death (5, 6), but perhaps surprisingly MEKK1 activates NFB pathways (7, 8) that induce expression of genes to counteract the apoptotic death response (9 -11).Stress activators upstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
0
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 25 publications
8
78
0
2
Order By: Relevance
“…We show that treatment with dicumarol, an inhibitor of NQOI, sensitized HeLa cells to Fas killing. This result is in agreement with earlier findings concerning the effect of dicumarol on apoptosis: it strongly potentiates TNF-a-induced apoptosis in HeLa cells (Cross et al, 1999); it abrogates the suppression of apoptosis by IGF-I in FL5.12 cells overexpressing wide-type (wt) insulin-like growth factor I receptor (IGF-IR) and it induces apoptosis in MCF-7 cells (Krause et al, 2001). Contradictory are the reports that overexpression of NQOI in MCF-7 sensitizes cells to TNF-a (Siemankowski et al, 2000) and that dicumarol blocks wt p53-mediated apoptosis in girradiated normal thymocytes and in Ml myeloid leukemic cells that overexpress wt p53 (Asher et al, 2001).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We show that treatment with dicumarol, an inhibitor of NQOI, sensitized HeLa cells to Fas killing. This result is in agreement with earlier findings concerning the effect of dicumarol on apoptosis: it strongly potentiates TNF-a-induced apoptosis in HeLa cells (Cross et al, 1999); it abrogates the suppression of apoptosis by IGF-I in FL5.12 cells overexpressing wide-type (wt) insulin-like growth factor I receptor (IGF-IR) and it induces apoptosis in MCF-7 cells (Krause et al, 2001). Contradictory are the reports that overexpression of NQOI in MCF-7 sensitizes cells to TNF-a (Siemankowski et al, 2000) and that dicumarol blocks wt p53-mediated apoptosis in girradiated normal thymocytes and in Ml myeloid leukemic cells that overexpress wt p53 (Asher et al, 2001).…”
Section: Discussionsupporting
confidence: 83%
“…It is possible that in HeLa cells the basal levels of NQOI activity mediate a dicumarol sensitive, survival pathway. This pathway could be mediated by the survival factor NFkB as dicumarol inhibits NFkB activation in primary macrophages (Cross et al, 1999). Another potential mediator of this survival pathway is the mitogen-activated protein kinase (MAPK) as it was reported that dicumarol blocks MAPK activation in HeLa cells (Cross et al, 1999) and inhibition of the MAPK cascade sensitizes HeLa cells to Fas-induced apoptosis (Holmstrom et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The JNK inhibitor SP600125 has previously been shown to markedly inhibit JNK activation by various agents. 33 A 48-h treatment of NB4 cells with 5 mM SP600125 inhibits the As 2 O 3 -mediated induction of c-jun expression, which is JNK-dependent (data not shown), demonstrating that 5 mM is an effective inhibitory dose. We treated NB4 cells with the combination of As 2 O 3 or darinaparsin (0.5 and 1 mM) and SP600125 (5 mM) to determine whether inhibition of JNK activity repressed As 2 O 3 or darinaparsin-induced growth Darinaparsin is more potent than As 2 O 3 in vitro Z Diaz et al inhibition.…”
Section: Jnk Activation Mediates Apoptosis Induced By Both As 2 O 3 Amentioning
confidence: 99%
“…The quinone reductase inhibitors dicoumarol and menadione block SAPK/JNK and NF-κB, and thereby potentiate apoptosis (Cross et al,1999). Javelaud and Besancon demonstrated that the repression of JNK activation by NF-κB is involved in the anti-apoptotic effect of this transcription factor in TNF α-treated Ewing sarcoma cells (Javelaud and Besancon, 2001).…”
Section: Anti-apoptotic Effects Of Nf-κbmentioning
confidence: 99%